Bipolar androgen therapy plus olaparib in men with metastatic castration-resistant prostate cancer - Schweizer, Michael T.; Gulati, Roman; Yezefski, Todd; Cheng, Heather H.; Mostaghel, Elahe; Haffner, Michael C.; Patel, Radhika A.; De Sarkar, Navonil; Ha, Gavin; Dumpit, Ruth; Woo, Brianna; Lin, Aaron; et al. (Prostate cancer and prostatic diseases, 2023)
Background Bipolar androgen therapy (BAT) results in rapid fluctuation of testosterone (T) between near-castrate and supraphysiological levels and has shown promise in metastatic castration-resistant prostate cancer (mCRPC). Its clinical effects may be mediated through induction of DNA damage, and preclinical studies suggest synergy with PARP inhibitors. Patients and methods This was a single-center, Phase II trial testing olaparib plus BAT (T cypionate/enanthate 400 mg every 28 days) with ongoing androgen deprivation. Planned recruitment was 30 subjects (equal proportions with/without homologous recombination repair [HRR] gene mutations) with mCRPC post abiraterone and/or enzalutamide. The primary objective was to determine PSA 50 response (PSA decline ≥50% from baseline) rate at 12-weeks. The primary analysis utilized the entire (intent-to-treat [ITT]) cohort, with those dropping out early counted as non-responders. Secondary/exploratory analyses were in those treated beyond 12-weeks (response-evaluable cohort). Results Thirty-six patients enrolled and 6 discontinued prior to response assessment. In the ITT cohort, PSA 50 response rate at 12-weeks was 11/36 (31%; 95% CI 17–48%), and 16/36 (44%, 95% CI 28–62%) had a PSA50 response at any time on-study. After a median follow-up of 19 months, the median clinical/radiographic progression-free survival in the ITT cohort was 13.0 months (95% CI 7–17). Clinical outcomes were similar regardless of HRR gene mutational status. Conclusions BAT plus olaparib is associated with high response rates and long PFS. Clinical benefit was observed regardless of HRR gene mutational status.